INTEGRATED MANAGEMENT SYSTEM FOR A SOCIETY FROM INDUSTRY OF MACHINERY AND EQUIPMENT - Constanţa RĂDULESCU (Fiabilitate şi Durabilitate)
In this paper shows the importance that it has SMI in a society of the industry of machinery and equipment. An integrated management system is the mode to design, implement and certify two or more management systems: Quality - Environment, Quality -Environment - Safety and Occupational Health. By implementing the system, the society themselves hires in the development and continuous improvement of the system in accordance with the ones three standards and with objective of activity of the society. Also, in the paper themselves presents the advantages and disadvantages of implementing this integrated system.